Effect of Different Auxins on the Establishment of Da mask Rose Cuttings in Different Media (Biological Sciences - PJSIR, 2007)
. Effect of i ndole-3-aceti c acid and n aphthal ene acet ic acid treatments  on  the  establ ish ment  of damask  rose ( Rosa  damascena  M i l l.) cutti ngs  i n  d i fferent growth  med i a was eva l u ated an d  it was revea led  that the  average n u mber  of roots  and  root i ng  percentage  grad uall y  i ncreased with  i ncrease  i n  hormone  concentrati on. The maxi m u m n u m ber of roots ( 1 5.72), rooti ng percentage (94.1 7 %), p l ant height ( 1 34.2  cm), p l ant  spread  (46.3  cm), pri mary shoots  (6.3),  secondary  shoots  (25)  and  survival  percentage  (94.72%)  was  recorded  for  50  mg/I   naphthalene   acetic  acid appl ication; the results were superior to i ndol e-3-acetic acid, t h e optim um l evel bei n g i n the range of 50 and 75 mg/I. o such concl usion  could be d rawn  for i ndol e-3-acetic acid. The leaf mold was the best growth medi um gi vi ng the max im um n umber of roots per cu tti ng (10.78), rooti ng percenta ge  (87.68%),  pl ant  h eight  ( 1 25 . 1 cm),  pl ant spread  (37  cm), pri mary  shoots  (5.2), secondary  shoots  ( 1 9.48)  and  surv i va l   percent age  (85.67%),  fol lowed  by  soi l+ leaf  mold , whi le soi l  med i um  was  the  l east  effective .